Promoting Healthy Eating among Young People-A Review of the Evidence of the Impact of School-Based Interventions - Chaudhary, Abina; Sudzina, František; Mikkelsen, Bent Egberg (Nutrients, 2020)
INTRO: Globally, the prevalence of overweight and obesity is increasing among children and younger adults and is associated with unhealthy dietary habits and lack of physical activity. School food is increasingly brought forward as a policy to address the unhealthy eating patterns among young people. AIM: This study investigated the evidence for the effectiveness of school-based food and nutrition interventions on health outcomes by reviewing scientific evidence-based intervention studies amongst children at the international level. METHODS: This study was based on a systematic review using the PRISMA guidelines. Three electronic databases were systematically searched, reference lists were screened for studies evaluating school-based food and nutrition interventions that promoted children's dietary behaviour and health aiming changes in the body composition among children. Articles dating from 2014 to 2019 were selected and reported effects on anthropometry, dietary behaviour, nutritional knowledge, and attitude. RESULTS: The review showed that school-based interventions in general were able to affect attitudes, knowledge, behaviour and anthropometry, but that the design of the intervention affects the size of the effect. In general, food focused interventions taking an environmental approach seemed to be most effective. CONCLUSIONS: School-based interventions (including multicomponent interventions) can be an effective and promising means for promoting healthy eating, improving dietary behaviour, attitude and anthropometry among young children. Thus, schools as a system have the potential to make lasting improvements, ensuring healthy school environment around the globe for the betterment of children's short- and long-term health.
Keywords: obezita dětí a dospívajících; Overweight; dítě; předškolní dítě; Adolescent; stravovací zvyklosti; lidé; školy; School Health Services; Schools; Humans; zdravé chování; složení těla; Feeding Behavior; Child, Preschool; nadváha; index tělesné hmotnosti; Health Knowledge, Attitudes, Practice; zdraví - znalosti, postoje, praxe; Body Composition; zdravá strava; Child; školní zdravotnické služby; Body Mass Index; Diet, Healthy; mladiství; Pediatric Obesity; Health Behavior